Optimization of hardness behaviour of TIG modified ceramic coating using the taguchi approach - Bello, Kamilu Adeyemi; Maleque, Md. Abdul; Ahmad, Zuraida; S. , Mirdha (Trans Tech Publications, Switzerland, 2015)

(untitled)
The increasing need for energy efficient tribo-composite surfaces has led to the enhancement of surface properties of engineering components through parameter processing control. This study was carried out to investigate the hardness behaviour of low alloy steel (LAS) surface modified with TiC under a tungsten inert gas (TIG) arc torch. The effects of welding current, traversing speed, arc voltage and argon flow rate on surface hardness during the surface alloying treatment were analyzed using Taguchi’s experimental design. The hardness behaviour of the TIG-processed composite coating was assessed with a Wilson Wolpert microhardness machine. The analysis of the experimental results based on the Taguchi’s design revealed that the welding speed and welding voltage are the most significant process parameters influencing the surface hardness performance of the composite coated layer. The signal-to-noise response was used to identify the optimum parameter combination for maximizing the surface quality characteristics. The validity of this approach was confirmed based on the good agreement between the predicted value and experimental result obtained at the tested optimal conditions.